Carotid Atherosclerosis Predicts Blood Pressure Control in Patients With Hypertension: The Campania Salute Network Registry - Costantino Mancusi; Maria Virginia Manzi; Giovanni de Simone; Carmine Morisco; Maria Lembo; Emanuele Pilato; Raffaele Izzo; Valentina Trimarco; Nicola De Luca; Bruno Trimarco (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The 2018 European Society of Cardiology/European Society of Hypertension arterial hypertension guidelines do not recommend routine carotid ultrasound as a tool to identify hypertension‐mediated organ damage, unless clinically indicated. However, carotid plaque (CP) is a strong correlate of increased arterial stiffness, which influences blood pressure (BP) control over time. Thus, we assessed whether evidence of CP at first visit could predict BP control during follow‐up. Methods and Results From the CSN (Campania Salute Network) Registry, 6684 patients with hypertension had complete carotid ultrasound examination and were categorized by the presence of CP at baseline. Optimal BP control was defined as average BP <140/90 mm Hg and <135/85 during follow‐up for office and home BP, respectively. At baseline, participants with CP (n=3061) were more likely to be men, to be older, to have diabetes, and to exhibit higher systolic BP, lower diastolic BP, worse lipid profile, and higher prevalence of left ventricular hypertrophy (all P<0.0001) than patients without CP. Optimal office BP control was adjudicated in 54% with and 62% without CP (P<0.0001), and optimal home BP in 51% with and 58% without CP (P<0.01). Presence of CP was significantly associated with the reduced probability of controlled office BP during follow‐up (both P<0.0001), independently of significant effect of older age, male sex, higher baseline BP values, classes of medication, and presence of left ventricular hypertrophy, and only attenuated by duration of hypertension. Conclusions Presence of CP in treated patients with hypertension is associated with suboptimal BP control during follow‐up, independently of worse metabolic profile and presence of left ventricular hypertrophy.